2013
DOI: 10.1088/0004-637x/771/1/21
|View full text |Cite
|
Sign up to set email alerts
|

DETECTING NANOFLARE HEATING EVENTS IN SUBARCSECOND INTER-MOSS LOOPS USING Hi-C

Abstract: The High-resolution Coronal Imager (Hi-C) flew aboard a NASA sounding rocket on 2012 July 11 and captured roughly 345 s of high-spatial and temporal resolution images of the solar corona in a narrowband 193 Å channel. In this paper, we analyze a set of rapidly evolving loops that appear in an inter-moss region. We select six loops that both appear in and fade out of the Hi-C images during the short flight. From the Hi-C data, we determine the size and lifetimes of the loops and characterize whether these loops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
72
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 32 publications
15
72
0
Order By: Relevance
“…The initial brightening represents a nanoflare that subsequently caused the second brightening through a heating pulse in the loop. This is supported by the results of Winebarger et al (2013), who found that cool dense loops were impulsively heated by nanoflares. …”
Section: Introductionsupporting
confidence: 68%
“…The initial brightening represents a nanoflare that subsequently caused the second brightening through a heating pulse in the loop. This is supported by the results of Winebarger et al (2013), who found that cool dense loops were impulsively heated by nanoflares. …”
Section: Introductionsupporting
confidence: 68%
“…Alternatively, energy can propagate downward as energetic particles that can penetrate into the high chromosphere: such particle precipitations are likely more intermittent as they rapidly shift in position. Recent high-resolution observations in the transition region show direct evidence of this type of process (under some magnetic-field conditions) in active regions (Testa et al, 2013;Winebarger et al, 2013). Other recent studies suggest that heating to coronal temperatures may occur primarily in the chromosphere and transition region, as evidenced, e.g.…”
Section: Currents and Reconnectionmentioning
confidence: 88%
“…Not surprisingly, many regions that show strong, transient substructure have already been the subject of analysis, including loops Winebarger et al 2013), dynamics in the moss (Testa et al 2013), evolution in the filament (Alexander et al 2013), and anomalous brightenings (Régnier et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have compared the properties of structures observed with Hi-C to the structures observed with the lower-resolution Atmospheric Imaging Array (AIA) on the Solar Dynamics Observatory (SDO; see, for instance, Cirtain et al 2013;Morton & McLaughlin 2013;Testa et al 2013;Winebarger et al 2013;Peter et al 2013;Brooks et al 2013;Alexander et al 2013;Régnier et al 2014). Two of these studies specifically focus on comparing the widths of linear structures, or coronal loops, in Hi-C and AIA data.…”
Section: Introductionmentioning
confidence: 99%